Factors Associated with the Incidence of Stress Urinary Incontinence in Uterine Prolapse Cases at RSUD Dr. Soetomo Surabaya - Eighty Mardiyan Kurniawati; Romi Kiki Nur Fita Sari (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: Urinary incontinence (UI) is the involuntary leakage of urine, which can cause problems and have a negative impact on quality of life. Stress urinary incontinence is one of the subtypes of urinary incontinence which is defined as the involuntary expulsion of urine during exertion or physical activity, or sneezing, or coughing. The purpose of this study was to explain the relationship between age, type of delivery, parity, and body mass index with the incidence of stress urinary incontinence in cases of uterine prolapse at RSUD Dr Soetomo Surabaya.Method: This type of research is a quantitative research using analytical observational method, with a cross sectional approach. The sampling technique in this study was total sampling that met all inclusion and exclusion criteria. The independent variables of this study were age, type of delivery, parity, and body mass index. The dependent variable of this study is stress urinary incontinence.Result: Fisher's Exact test results on age, type of delivery, parity, and body mass index obtained p-values of 0.004, 0.021, 0.021, 0.014, 0,014 respectively. Because the p value of the five variables > 0.05, it can be concluded that H1 is accepted.Conclusion: There is a relationship between age, type of delivery, parity, body mass index, and degree of uterine prolapse. The results of the logistic regression test showed that most related variable to the incidence of stress urinary incontinence was age.